2023
DOI: 10.1021/acsami.3c05177
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Recognition by Supramolecular Porphyrin–Hemicucurbit[8]uril-Functionalized Gravimetric Sensors

Abstract: Enantiorecognition of a chiral analyte usually requires the ability to respond with high specificity to one of the two enantiomers of a chiral compound. However, in most cases, chiral sensors have chemical sensitivity toward both enantiomers, showing differences only in the intensity of responses. Furthermore, specific chiral receptors are obtained with high synthetic efforts and have limited structural versatility. These facts hinder the implementation of chiral sensors in many potential applications. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In this context, our focus is to develop chiral chemical sensors based on rationally designed sensing materials, intending to fill the existing gap between the production of enantioselective receptors and the realization of macroscopic devices being able to work in real scenarios. As an example of such sensors, we have recently reported that sensing layers consisting of metalloporphyrins combined with chiral cyclohexanohemicucurbit [8]urils deposited on quartz microbalances efficiently recognize vapor samples of limonene and 1-phenylethylamine enantiomers by application of a novel normalization procedure and multivariate analysis techniques to improve the classification performances. 8 In this paper, we report new chiral nanosystems by integrating porphyrin-based receptors into silica nanohelices.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, our focus is to develop chiral chemical sensors based on rationally designed sensing materials, intending to fill the existing gap between the production of enantioselective receptors and the realization of macroscopic devices being able to work in real scenarios. As an example of such sensors, we have recently reported that sensing layers consisting of metalloporphyrins combined with chiral cyclohexanohemicucurbit [8]urils deposited on quartz microbalances efficiently recognize vapor samples of limonene and 1-phenylethylamine enantiomers by application of a novel normalization procedure and multivariate analysis techniques to improve the classification performances. 8 In this paper, we report new chiral nanosystems by integrating porphyrin-based receptors into silica nanohelices.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As an example of such sensors, we have recently reported that sensing layers consisting of metalloporphyrins combined with chiral cyclohexanohemicucurbit [8]urils deposited on quartz microbalances efficiently recognize vapor samples of limonene and 1-phenylethylamine enantiomers by application of a novel normalization procedure and multivariate analysis techniques to improve the classification performances. 8 In this paper, we report new chiral nanosystems by integrating porphyrin-based receptors into silica nanohelices. Indeed, nanoscale siliceous materials offer a number of potential advantages for sensing applications, thanks to their stable structural and functional properties, 9−11 also in combination with organic dyes like porphyrins.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chirality is fundamental to molecules and nature, which plays a crucial role in various biological processes, chiral separation, chiral detection, chiral recognition, and asymmetric catalysis . Although chirality at the molecular level is well studied, however, transferring chirality from the molecular level to nanomaterials has opened up cutting-edge research areas in chiral nanomaterials. , Incorporating chirality in nanomaterials makes them unique candidates for biological sensing, photonics, and fabrication of spin-polarized optoelectronic devices .…”
Section: Introductionmentioning
confidence: 99%
“…Chirality sensing adds another viewpoint to sensing systems, and we have shown that toxic organocatalysts can be sensed via complex formation with Zn porphyrins [6]. By merging chiral hemicucurbiturils and metalloporphyrins via noncovalent interactions into a solid thin material, one can construct an enantioselective electronic nose and very selectively discriminate different analytes and their handedness [7]. In this conference, we will present our findings on how hemicucurbiturils and porphyrins, as supramolecular receptors, can be employed for optical and gravimetric sensing, as well as for the remediation of chemical pollutants.…”
mentioning
confidence: 99%